2015
DOI: 10.1177/0741932515581494
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences as Predictors of State Accountability Measures of Schools’ Facilitation of Parent Involvement

Abstract: The aim of this study was to ascertain which dimensions of parents' experiences with schools are most strongly associated with parents' perceptions that schools are or are not facilitating parent involvement as mandated by the federal accountability system under the Individuals With Disabilities Education Act (IDEA). Participants were 92 parents of students with disabilities from 18 schools in 8 school districts in a large southeastern state. Parents completed the quantitative measure used by their state to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 47 publications
0
37
0
1
Order By: Relevance
“…While perhaps unintentional, this type of wording suggests the limited nature of parent membership on IEP teams. Yet IDEA continues to center parents as key members of the IEP team (2004), and research confirms their critical role in IEP development (Elbaum et al, 2016;Francis, Hill, Blue-Banning, Turnbull, & Haines, 2016).…”
Section: Key Findingsmentioning
confidence: 99%
“…While perhaps unintentional, this type of wording suggests the limited nature of parent membership on IEP teams. Yet IDEA continues to center parents as key members of the IEP team (2004), and research confirms their critical role in IEP development (Elbaum et al, 2016;Francis, Hill, Blue-Banning, Turnbull, & Haines, 2016).…”
Section: Key Findingsmentioning
confidence: 99%
“…In their study, Ben-Yehuda, Leyser and Last (2010) determined that teachers successful in increasing the social interaction of children with special needs acquainted themselves with the child's past and established meaningful and positive relationships with their families. Another study found that parent-school collaboration was an important factor affecting parents' opinions of the school (Elbaum, Blatz & Rodriquez, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this view, a few parent stated that they are not desire to involve every IEP process as the agenda was prepare in advance and there is no balance between IEP objective and school performance [57]. In this regard, Hammond [61] showed that almost all parents indicated that being involved in their child's educational program was a crucial factor that parents should perform in their child's education.…”
Section: Parental Communication With Teachers and School Staffmentioning
confidence: 99%
“…In this regard, Hammond [61] showed that almost all parents indicated that being involved in their child's educational program was a crucial factor that parents should perform in their child's education. The interview study performed by Blue-Banning, et al [62] identified six themes associated to collaborative familyschool partnerships: communication, commitment, equality, skills, trust, and respect Elbaum [57]. As Epstein [37] propose, what is needed in schools is an extensive system of parental involvement.…”
Section: Parental Communication With Teachers and School Staffmentioning
confidence: 99%
See 1 more Smart Citation